Limitation Of Authority Between Central And Local Governments In The Oil And Gas Business - Wulan, Dewi Nawang; Rusydi; Ahmad Munir; Ahmad Taufiq Rifaldi (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
The oil and gas revenue-sharing system for several regions has conflicting norms for regulating authority between the central government and regional governments in the oil and gas revenue-sharing system for several regional governments. In Article 14 Paragraph 3 of Law Number 23 of 2014 concerning Regional Government it is stated that only the central government can manage oil and gas business activities. -Law Number 22 of 2001 concerning Oil and Gas still regulates the authority/involvement of local governments in fulfilling the clauses of the cooperation contract as an instrument of oil and gas business activities. The method used in writing this article is normative law. In this study, the authors want to know and obtain clarity about what the central authority over the oil and gas business is, and how the revenue-sharing funds are divided for the two local governments. The literature used in this paper comes from scientific journals and is supported by scientific books from various scientists. From the results of the research that has been done, in fact there is still involvement of local governments both in management in the form of fulfilling the clauses of the cooperation contract, especially in determining the work area and its return as well as environmental management.